2016
DOI: 10.1186/s12931-016-0401-0
|View full text |Cite
|
Sign up to set email alerts
|

Relative impact of COPD and comorbidities on generic health-related quality of life: a pooled analysis of the COSYCONET patient cohort and control subjects from the KORA and SHIP studies

Abstract: BackgroundHealth-related quality of life (HRQL) is an important patient-reported outcome measure used to describe the burden of chronic obstructive pulmonary disease (COPD) which is often accompanied by comorbid conditions.MethodsData from 2275 participants in the COPD cohort COSYCONET and from 4505 lung-healthy control subjects from the population-based KORA and SHIP studies were pooled. Main outcomes were the five dimensions of the generic EQ-5D-3 L questionnaire and two EQ-5D index scores using a tariff bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
3
23
0
2
Order By: Relevance
“…238 In females, associations found in the total population for mobility and usual activities with 239 FEV 1 and FVC remained significant (mobility: FEV 1 : β= -81 ml; FVC: β= -109 ml; usual 240 activities: FEV 1 : β= -86 ml; FVC: β=-106 ml) (S1 Table A2). Results for males showed similar 241 estimates, but were significant only for the association between FEV 1 were obtained when applying GLI z-scores (Tables A4 and A5 in S1 Tables). 247 248 Effect modification between EQ-5D dimensions and physical inactivity 249 Physical inactivity showed weak correlations with the EQ-5D dimensions, with the highest 250 correlations observed with anxiety/depression and mobility problems (Cramér's V 0.16 and 251 0.15, respectively).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…238 In females, associations found in the total population for mobility and usual activities with 239 FEV 1 and FVC remained significant (mobility: FEV 1 : β= -81 ml; FVC: β= -109 ml; usual 240 activities: FEV 1 : β= -86 ml; FVC: β=-106 ml) (S1 Table A2). Results for males showed similar 241 estimates, but were significant only for the association between FEV 1 were obtained when applying GLI z-scores (Tables A4 and A5 in S1 Tables). 247 248 Effect modification between EQ-5D dimensions and physical inactivity 249 Physical inactivity showed weak correlations with the EQ-5D dimensions, with the highest 250 correlations observed with anxiety/depression and mobility problems (Cramér's V 0.16 and 251 0.15, respectively).…”
mentioning
confidence: 68%
“…Thus, prevention of inactivity appears to 28 be reasonable even in lung-healthy adults. 29 30 31Health-related quality of life (HRQL) is reduced in patients with chronic lung diseases such as 32 chronic obstructive pulmonary disease (COPD) [1][2][3]. While various factors, including 33 impaired lung function, can lead to a decrease in HRQL with increasing disease severity, 34 physical activity has been found to be associated with better HRQL as well as less hospital 35 admissions in COPD [2,[4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 and Figure 4 show that the intervention was not significantly associated with a change in cardiorespiratory, COPD-related, cardiovascular or respiratory emergency admissions for people of all ages. The results include summaries of the raw, unadjusted data for the pre-and post-intervention phases, and the paired differences for those [18,527] 0.0543 (0.4788) [22,209] 0.0152 (0.9144) [12, [18,527] 0.0062 (0.1468) [22,209] 0.0054 (0.1526) [12, [18,527] 0.0179 (0.2709) [22,209] 0.0108 (0.5264) [12, [18,527] 0.0324 (0.3720) [22,209] 0.0045 (0.7374) [12, people who were in the study for both phases (irrespective of the lengths of residency periods). We subsequently included covariates and factors in univariate linear models for each outcome, and the adjusted comparisons are taken from models that retain all significant covariates and factors (listed at the end of Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] However, because of the heterogeneity of COPD and the comorbid conditions that are often associated with it, researchers and practitioners have begun to use generic HRQOL measures in conjunction with disease-specific measures to evaluate outcomes of various interventions. [9][10][11][12] For example, Engström et al 13 argued that disease-specific HRQOL measures were not sufficient to examine the effect of COPD on life functions due to comorbidities frequently seen in the COPD population. In a study that assessed the HRQOL in individuals with varying severity of COPD, the researchers found that disease-specific HRQOL indicators correlated well with measures of lung function, but generic HRQOL indicators that measure emotional status and psychosocial function correlated poorly with measures of lung function.…”
Section: Introductionmentioning
confidence: 99%